Exploring Herbal Therapies for Diabetes: A Review of Promising Medicinal Plants (International Journal of Food and Nutritional Sciences, 2022)
Diabetes is a metabolic disorder characterized by elevated blood sugar levels, which occurs as a result of defects in insulin secretion or action, or both. There are two main categories of diabetes, namely type 1 and type 2. Risk factors for diabetes include genetics, obesity, hypertension, and others. Although conventional drugs like biguanides, sulfonylureas, and meglitinides are commonly prescribed for treatment, achieving desired effectiveness can still be challenging. Hence, researchers are exploring alternative therapies for diabetes. Medicinal plants have shown promise and are extensively used in India for the prevention and treatment of diabetes. This review article focuses on highlighting herbs that have been reported to possess significant antidiabetic properties